Acute coronary stent thrombosis: A case of type 3 Kounis syndrome. Issue 1 (January 2019) - Tripolino, Cesare; Tassone, Eliezer Joseph; Morabito, Gaetano; Grillo, Placido; Missiroli, Bindo
Abstract: Kounis syndrome refers to an acute coronary syndrome, consequent to an allergic reaction. It results from mast cell degranulation with subsequent release of numerous inflammatory mediators, leading to coronary vasospasm, atheromatous plaque rupture, or stent thrombosis. Here, we describe the case of a 47-year-old Caucasian man with acute stent thrombosis, as a consequence of allergic reaction to contrast media. <Learning objective: Kounis syndrome is an acute coronary syndrome, consequent to an allergic reaction. Cytokine release might precipitate coronary spasm, plaque rupture, or stent thrombosis. Stent thrombosis is a dramatic complication of coronary stenting, presenting as sudden death or acute myocardial infarction. Our case serves as an example for clinicians to consider the possibility of Kounis syndrome in patients with acute coronary syndrome and anaphylaxis in order to ensure appropriate treatment.>